A retrospective analysis of neuroendocrine tumour of pancreas: a single institute study - Chheda, Yogen P.; Arora, Deeksha; Patel, Rutul (International Journal of Research in Medical Sciences, 2017)
Background: The aim of the work was the clinical characteristics and analysis of preliminary results for surgical treatment of pancreatic neuroendocrine tumors (PNETs). This article deals with the classification of the Pancreatic Neuroendocrine Tumors (PNETs) and discusses their presentation, behaviour, treatment and prognosis. Methods: This was a retrospective study of 70 patients of PNET done over a period of 3 years in The Gujarat Cancer and Research Institute, Ahmedabad. 24 patients who underwent surgical treatment for PNET were further evaluated for surgical outcome, 5yr disease free survival and overall survival. Results: In this study of 70 patients, 61(87.14%) were non-functional. Approximately 77% of PNETs were advanced on presentation (57% metastatic and 20% locally advanced). 20 patients had disease resectable on presentation (11 NF + 9 F). These 20 patients belong to stage I and II of TNM staging system. Only 4 out of 40 metastatic diseases had locally resectable tumor. Of 24 patients who underwent surgery, 12 underwent pancreatico-duodenectomy, 6 underwent enucleation and 6 underwent distal pancreatectomy. Conclusions: PNETs are uncommon tumor of pancreatic origin with presentation more commonly in males than females, usually in the 5th decade. Approximately 77% of patients are advanced or metastatic at presentation. Among those resectable, the Overall Survival for FPNETs and NFPNETs was 90% and 94% respectively and 5yr Disease Free Survival for the same was 100% and 84% respectively.